Evaluation of mtDNA stability across the maternal line: A study on three generations in two families. (December 2015) - Cortellini, V.; Verzeletti, A.; Cerri, N.; Cisana, S.; De Ferrari, F.
Abstract: Sometimes deficiency paternity testing can not be resolved with routine STR analysis and nuclear DNA fails to give conclusive results. In these cases, mitochondrial DNA (mtDNA) analyses have been proved more effective. In general, mtDNA transmission is stable across many generations; therefore the mtDNA typing allows to assess maternal relationships, even in deficiency cases. To evaluate the consistency of mtDNA, we compared HVI and HVII regions in three generations along the maternal line (great-grandmother, grandmother, mother, daughter or son) in two families, confirming the useful of this marker in such cases.